Ionising radiation and trans-generational instability - Vrhovac, Ivana (Radiology and oncology (Ljubljana), 2007)
Background. Indirect monitoring of the impact posed by ionising radiation to the genome instability of the descendants, consequent to the irradiation of one of their parents, boils down to the investigation of changes occurring exclusively in the mini-satellite loci of the cells constituting the gametal developmental line. The resultant mini-satellite mutations are expressed in their percentages, and equal to the ratio of the number of mutated alleles in that particular generation over the total number of alleles present. The impact of ionising radiation to the irradiated parentćs offspring was first noticed on haematopoietic mouse stem-cells. Even though an irradiated cell of a female parent lacks any mutations whatsoever, daughter cells present with the increased mutation rates. The observed phenomenon of the so called trans-generational instability has been defined as the occurrence of mutationsin the genome of individuals originating from the irradiated ancestors. Due to the aforementioned, one can conclude that these mutations need not be present in the irradiated parental cells, and do not necessarily vanish in the next few generations, but may result in the increase in mutationrates observed in the latter. Conclusions. The results of the investigations performed on the animal model, as well as of those carried out in human population, point to the occurrence of significant changes to be found on mini-satellite loci of the descending generation, while the mechanismunderlying those changes hasnćt been completely clarified yet, and, therefore, calls for the further investigation.
Keywords: Bolezen, živalski modeli; celice; Disease Models, Animal; Genetics; ionizirajoče sevanje; Microsatellite Repeats; Mikrosatelitne ponovitve; Mutacija; mutacije; Mutation; Radiation Effects; Radiation, Ionizing; Sevane ionizirajoče; sevanje; Sevanje, učinki; vpliv